Analysis of Rainfall Effect on Slope Failure in Sabah - Siti Jahara, Matlan; Nazaruddin, Abdul Taha; Salinah, Dullah; Mohammad Radzif, Taharin; Hasmida, Hamza (Construction Research Institute of Malaysia (CREAM), 2021)
The paper is aimed to characterize the relationship between the landslide events and the critical rainfall intensity-duration from the rainfall analysis. In this study, 10 landslide events that occurred in Ranau, Sabah area between years 2007 to 2015 were investigated and analysed using rainfall threshold based on soil water index (SWI) method. The analysis results showed that both short-intense rainfall (i.e., 1-day) and prolonged antecedent rainfall (i.e., 14, 30-day) played a significant role of the landslide initiations in Ranau, Sabah area. Overall results indicated that this method could simulate the rain infiltration response by the level of soil moisture in the area of landslide.